BLOOD PRESSURE VARIATIONS DURING DIFFERENT HOSPITAL SHIFTS AND THEIR IMPACT ON HEALTHCARE PROFESSIONALS - Dr. Laxmi Bhandari; Dr. Khwaja Mohd. Amir; Dr. Ashwin K Abraham; Dr. Ankit Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Healthcare professionals frequently experience demanding work schedules characterized by shift rotations that can significantly impact cardiovascular health. This study aimed to assess blood pressure variations among healthcare professionals during different hospital shifts and evaluate their association with work-related factors and health outcomes. Methods: This prospective cross-sectional study with longitudinal components was conducted at Autonomous State Medical College, Sonebhadra, over six months (October 2024-March 2025). A stratified random sample of 150 healthcare professionals (physicians, nurses, and allied health staff) underwent blood pressure measurements across different shifts using standardized protocols. Participants completed 24-hour ambulatory blood pressure monitoring during one complete rotation cycle. Work-related factors and health parameters were assessed using validated questionnaires. Statistical analysis included repeated measures ANOVA and multiple linear regression models. Results: Night shifts were associated with the most pronounced blood pressure elevations across all professional categories (end-of-shift SBP/DBP: 138.7/88.3 mmHg vs. 130.1/83.7 mmHg for morning shifts, p=0.003). Rotating shift workers exhibited significantly higher rates of non-dipping and reverse dipping patterns (59.6% vs. 39.1%, p=0.003) and higher prevalence of sustained hypertension (33.7% vs. 19.6%, p=0.018) compared to day shift workers. Consecutive night shifts (β=2.41 mmHg, p<0.001), reduced sleep duration (β=1.94 mmHg, p<0.001), and job strain (β=1.24 mmHg, p<0.001) independently predicted blood pressure elevation. Healthcare professionals with hypertension reported poorer sleep quality, reduced quality of life, increased absenteeism, and higher rates of self-reported medical errors. Conclusion: Significant blood pressure variations occur among healthcare professionals during different hospital shifts, with night shifts and rotating schedules associated with concerning cardiovascular risk profiles. These findings highlight the need for targeted interventions to mitigate shift work’s impact on blood pressure regulation and subsequently improve both healthcare worker wellbeing and patient care quality.